2023
DOI: 10.3389/fbioe.2023.1170676
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of enzymolysis of silkworm pupa protein after tri-frequency ultrasonic pretreatment: kinetics, thermodynamics, structure and antioxidant changes

Abstract: As a by-product of the sericulture industry, the utilization rate of silkworm pupa resources is currently not high. Proteins are converted into bioactive peptides through enzymatic hydrolysis. Not only can it solve the utilization problem, but it also creates more valuable nutritional additives. Silkworm pupa protein (SPP) was pretreated with tri-frequency ultrasonic (22/28/40 kHz). Effects of ultrasonic pretreatment on enzymolysis kinetics, enzymolysis thermodynamics, hydrolysate structure as well as hydrolys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 50 publications
0
0
0
Order By: Relevance
“…Interestingly, with regard to V max , contrary results were reported by some studies, where V max showed a slight downward trend [67,83,85]. K M is fundamental to the kinetics of the hydrolysis reaction, which is inversely proportional to the reaction rate: the lower the K M value, the faster the reaction rate [86]. Ariana de Souza Soares et al [51] came to a different conclusion, finding that ultrasound as a pretreatment method did not promote sucrose hydrolysis but slightly reduced the invertase activity.…”
Section: Effect Of Ultrasonic Pretreatment On Thermodynamic and Dynam...mentioning
confidence: 67%
“…Interestingly, with regard to V max , contrary results were reported by some studies, where V max showed a slight downward trend [67,83,85]. K M is fundamental to the kinetics of the hydrolysis reaction, which is inversely proportional to the reaction rate: the lower the K M value, the faster the reaction rate [86]. Ariana de Souza Soares et al [51] came to a different conclusion, finding that ultrasound as a pretreatment method did not promote sucrose hydrolysis but slightly reduced the invertase activity.…”
Section: Effect Of Ultrasonic Pretreatment On Thermodynamic and Dynam...mentioning
confidence: 67%